Complete Response to Combined Chemotherapy and Anti-PD-1 Therapy for Recurrent Gallbladder Carcinosarcoma: A Case Report and Literature Review - Liu, Qin-qin; Lin, Hao-ming; Han, Hong-wei; Yang, Cai-ni; Liu, Chao; Zhang, Rui (Frontiers in Oncology, 2022)
Background Gallbladder carcinosarcoma (GBCS) is a rare and aggressive malignancy with extremely poor prognosis. Although surgery is regarded as the primary therapy for GBCS, the effective therapeutic strategies for unresected lesions have been poorly defined. Case Presentation We presented a case of a 74-year-old male who underwent radical resection of gallbladder carcinoma at a local hospital. Seven months later, he was admitted to our hospital due to right upper abdominal discomfort. Postoperative radiological examinations showed multiple hepatic lesions, hilar lymph node metastasis, and main portal vein tumor thrombus. The pathological consultation results confirmed GBCS and immunohistochemical examinations revealed PD-L1 expression in 20% of tumor cells. Then, the patient received chemotherapy (Gemcitabine plus Oxaliplatin, GEMOX) in combination with anti-PD-1 therapy. After nine courses of the combination therapy, complete regression of the tumors was achieved with no evidence of relapse till now. Conclusions We, for the first time, reported a patient with recurrent GBCS who benefited from the combined chemotherapy and immunotherapy, providing a potential effective management strategy for the refractory malignant tumor.